Associations between disrupted functional brain network topology and cognitive impairment in patients with rectal cancer during chemotherapy - Guo, Yesong; Liu, Siwen; Yan, Fei; Yin, Na; Ni, Jie; Li, Chenchen; Pan, Xuan; Ma, Rong; Wu, Jianzhong; Li, Shengwei; Li, Xiaoyou (Frontiers in Oncology, 2022)
Introduction: Cognitive impairment has been identified in non-central nervous system cancer patients received chemotherapy. Chemotherapy-induced brain changes were considered as the possible causes underlying the cognitive deficits of patients. The purpose of this study was to explore chemotherapy-related functional brain changes and cognitive impairment in rectal cancer (RC) patients who had undergone chemotherapy treatment. Methods: In this study, RC patients after chemotherapy treatment (n=30) and matched healthy controls (HCs) (n=30) underwent cognitive assessments, structural magnetic resonance imaging (MRI) and resting-state functional MRI. The functional brain network of each subject was constructed by thresholding the partial correlation matrices of 90 brain regions in the Anatomical Automatic Labeling template and the topologic properties were evaluated by the method of graph theory analysis. Moreover, correlations between altered topological measures and the scores of cognitive scales in the patient group were explored. Results: Compared with HCs, RC patients following chemotherapy had lower scores on cognitive scales. The functional brain network of patients had preserved small-world topological features but with a tendency towards higher path length in the whole network. The between-group comparison revealed that patients had decreased nodal global efficiency (Eglo(i)) in the left superior frontal gyrus (dorsolateral), superior frontal gyrus (orbital part), inferior frontal gyrus (opercular part), inferior frontal gyrus (triangular part) and right inferior frontal gyrus (triangular part). Additionally, values of Eglo(i) in the superior and inferior frontal gyrus were positively associated with the level of cognitive function in the patient group. Conclusion: These results suggested that cognitive impairment was associated with disruptions in the topological organization of functional brain networks in RC patients received chemotherapy and provided new insights into the underlying pathophysiology of chemotherapy related cognitive impairment.